Labour exploitation and work-based harm - Scott, Sam, (Lecturer in human geography) (Bristol, UK : Policy Press, 2018)
This book provides a critical understanding of contemporary forced labour as a global social problem and argues that it should be located within the broader study of work-based harm.
Includes bibliographical references and index.
Keywords: Forced labor; Unfair labor practices; Industrial relations